EDUCATION DEMOCRACY IN THE PHILOSOPHY OF ISLAMIC EDUCATION PERSPECTIVE - Abd Mukti; Junaidi Arsyad; Achmad Bahtiar (Proceeding International Seminar of Islamic Studies, 2022)
This paper expresses the meaning of democracy in Islamic education in depth by using a content study approach that is an in-depth analysis of the content of information from education experts. In an educational democracy, the values contained in the implementation of educational practices and programs of an educational institution consist of several stakeholders such as educators, education staff, students, principals and school committees or the community in order to achieve the same goals as contained in the vision. and the mission of educational institutions. Through efforts to implement democratic values, education is expected to be able to encourage people to become active, independent, creative, innovative, critical, productive individuals and respect others. The essence of democracy in Islamic education is to place the human position proportionally or there is a balance between educators and students in placing themselves and being able to carry out the educational process properly, by putting aside individual differences that are brought from birth and there is no element of compulsion or self-awareness in following education and eliminate all things that hinder the educational process to gain knowledge in order to achieve a high degree before Allah SWT and to achieve happiness in this world and in the hereafter.Keywords: Education Democracy, Islamic Education Philosophy